The range of peripapillary retinal nerve fibre layer and optic disc parameters in children aged up to but not including 18 years of age, as measured by optical coherence tomography: protocol for a systematic review. Issue 1 (December 2016) - Creavin, Alexandra; Williams, Cathy; Tilling, Kate; Timpson, Nicholas; Higgins, Julian
Abstract Background The parameters of the optic disc and peripapillary retinal nerve fibre layer (pRNFL) in children may vary with disease processes that contribute to visual impairment and blindness and so could be useful as an objective measure in at-risk children. There is no standardised reference for the normal parameters of the optic disc and pRNFL in children; however, there are a large number of small individual studies that have been undertaken to look at these measures. Methods A systematic review of current literature on the range of pRNFL and optic disc parameters in children aged less than 18 years will be performed. Studies will be considered for review if they report numerical data on optic disc and pRNFL parameters, measured using optical coherence tomography. Outcome measures will include mean pRNFL thickness and cup-disc ratio. The bibliographic databases Medline, CINAHL, EMBASE, Scopus and Web of Science will be systematically searched from 1991. Screening of search results will be conducted by two authors working independently, as will extraction of primary and secondary outcome data. Ten per cent of all other data extraction will be checked by a second author. Results will be compiled and presented in evidence tables. Where possible and appropriate, study-specific estimates will be combined to obtain an overall summary estimate of pRNFL thickness and cup-disc ratio across studies and results will be presented by age of population. Subgroup analyses will be undertaken for children of different ethnicities. Discussion This review aims to provide an overview of the parameters of the optic disc and pRNFL in children of different ages in order to identify gaps in knowledge and to improve understanding of what might be considered within/outside the range of normality. The findings will be presented in peer-reviewed journals and will be presented at conferences. Systematic review registration PROSPEROCRD42016033068